RANCANGAN MODUL PELATIHAN UNTUK IBU YANG MEMILIKI ANAK AUTIS - Hanoum, Magdalena (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2015)
This study aim to examine the knowledge of the mother who has autism kid about the characteristic and problem of autism child, and about the skill of these autism?s mother in handling the problem of their autism kids. After having the data about this things, the researcher arrrange a pre-modul of improving knowledge and skill for mother of autism training program. This study consist of two steps. First, to get a description and the profile of the knowledge and skill of the mother of autism. We get them for willing to involve in developing their kid?s potency. This knowledge and skill strongly related to the comprehension of the mother about the problems and handling autism child. Second, based on those description and profile, we make a pre-modul of improving knowledge and skill for mother of autism training program, in order to be used in a autism?s potency developmental activity, especially improving the IJA skill in autism children. From the questionnaire that given to the mother of autism kid, the data of characteristic of knowledge and skill of mother in a problem and handling autism children has been gotten. The mothers have adequate knowledge, also an ability to understand and accept the condition of their autism kid. They care about, pay attention, and take care of the autism children with a very restrictive knowledge and skill, which should be increased so that the development of their autism kid could be optimal. Hence, researcher arrange a pre-modul of improving knowledge and skill for mother of autism training program, especially in improving the IJA skill in autism children. This pre-modul training program expected to be the manual to support the program for the mothers with autism kid. Then, this pre-modul training program could improve the knowledge and skill of mothers, so that mothers would be able to apply the knowledge and skill from this training program in many settings of daily life with autism children